Requirements Change Management Using Agile Methods and Dev-Ops Team Management: An Article Review - Alsharari Abdullah Sabih D , Wan Mohd Nazmee Wan Zainon , Sukumar Letchmunan , Alsharari Mohammed Sabih D (International Journal of Advanced Science and Technology, 2020)
Software engineering experts define agile development as “the collaboration betweendifferent software engineering teams to achieve cross-functional tasks and increase the pace ofsoftware development through reducing time needed to fulfil requirements of the software. Thispaper review the current requirement change management in agile methods especially createdfor website engineering and highlight their strength and weaknesses. Besides, it will show thedesign of requirement change model based on agile methods that provide better requirementchange management for web projects to overcome the weaknesses of the current classical agilemethods, and finally we want to implement the modified requirement management model in orderto evaluate the effectiveness of the proposed model. Additionally, this study examines a modifiedversion of evaluation framework that assist in monitoring the Dev-Ops effects on performancemetrics; this framework proposes the use of different SE techniques such as slicing technique atthe source code level and pipeline tasking development paradigm. We use a systematic reviewmethod to answer our aim to capture the current state of the art in Agile RCM as well as the roleof Dev-Ops team style in improving the quality of Agile SE modeling. Then we definerequirements for pattern and model then we create a model to evaluate against predefinedrequirements.